2018
DOI: 10.1029/2018ja025914
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Our Knowledge of Inner Magnetosphere‐Ionosphere Convection

Abstract: Plasma convection in the coupled inner magnetosphere‐ionosphere is influenced by different factors such as neutral winds, penetration electric fields, and polarization electric fields. Several crucial insights about the dynamics in the region have been derived by interpreting observations in conjunction with numerical simulations, and recent expansion in ground‐ and space‐based measurements in the region along with improvements in theoretical modeling has fueled renewed interest in the subject. In this paper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License the E M field (Kivelson, 1976;He et al, 2010;Kunduri et al, 2018). These include the study of magnetospheric electric fields and their variation with geomagnetic activity, numerical simulations on the internal magnetosphere-ionosphere convection, the study of the small-scale magnetospheric electric field observed by the Double Star TC-1 satellite (Matsui et al, 2008;Kivelson, 1976).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License the E M field (Kivelson, 1976;He et al, 2010;Kunduri et al, 2018). These include the study of magnetospheric electric fields and their variation with geomagnetic activity, numerical simulations on the internal magnetosphere-ionosphere convection, the study of the small-scale magnetospheric electric field observed by the Double Star TC-1 satellite (Matsui et al, 2008;Kivelson, 1976).…”
Section: Introductionmentioning
confidence: 95%
“…Even today, only a few missions have included direct measurements of the magnetospheric electric field in high latitude regions such as the -Parker Solar Probe‖ mission launched on August 12, 2018 in Florida and -ESA S SMILE‖ class mission whose launch is scheduled for 2023. Therefore, many studies used data from the electric field on one hand and the magnetic field on the other hand, acquired at high latitudes (Kim et al, 2013;Kunduri et al, 2018) and at latitudes equatorial (Kelley et al, 1979;Fejer and Scherliess, 1995;Fejer et al, 2007). Since there is no way to determine directly the E M field overall distribution, various empirical and mathematical models have been provisionally constructed, with varying degrees of complexity (Wu et al, 1981;Pierrard et al, 2008;Matsui et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The second characteristic includes the rapid SW and IMF oscillations leading to IEF E Y oscillations and implying prevailing undershielding conditions due to the shielding E field's disturbed development (Kunduri et al., 2018). As shown in Figures 1a and 1b, the IEF E Y component oscillated between dawn‐to‐dusk ( E Y > 0 at southward IMF) and dusk‐to‐dawn ( E Y < 0 at northward IMF).…”
Section: Results and Interpretationmentioning
confidence: 99%
“…For modeling the orientation of the arcs during spring transitions, we would need data of neutral winds above 100 km, but we have no such data. In general, the neutral wind at these altitudes is poorly known (Kunduri et al., 2018). Obviously, the wind at 100–150 km may differ crucially from that measured at 90–100 km.…”
Section: Discussionmentioning
confidence: 99%
“…The electric field generated due to the dynamo processes depends on the neutral winds and distribution of ionospheric conductivity or electron density at 100–150 km. Unfortunately, we have no co‐located measurements of neutral winds above 100 km and, in general, one lacks enough such data because of difficulty of observations in this region (Kunduri et al., 2018). In the present paper, therefore, we may only qualitatively hypothesize how the neutral wind influences the ionosphere‐magnetosphere system.…”
Section: Discussionmentioning
confidence: 99%